Конструкторсько-технологічний аналіз польових гетеротранзисторів високої швидкодії для субмікронних структур ВІС/НВІС - Новосядлий, Степан Петрович; Бойко, Сергій Іванович (НТУ "ХПІ", 2015)
Проведено аналіз швидкодії гетероструктурних польових транзисторів із селективним легуванням (ПТГСЛ), багатоканальних ПТГСЛ та ПТГСЛ з оберненою структурою, а також польових транзисторів з гетерозатвором високої щільності. На практиці отримані ПТГСЛ із значенням часу затримки в кільцевому генераторі τD = 12,5-25 пс при Т= 300 К потужністю PD= 0,9-4,0 мВт. Використання таких транзисторів в комплементарних вентилях, дозволяє збільшити їх швидкодію в 2,5-3 раз, в порівнянні з кремнієвими.

This paper analyzes performance of heterojunction FETs for LSI/VLSI structures, namely heterojunction field-effect transistors with selective doping (MODFET), multichannel MODFET and MODFET with reverse structure, as well as field-effect transistors with high density heterogate. Main feature of MODFET is a very high conductivity and quantum states in a fairly narrow channel, and also close proximity of metal gate to the channel with a large dielectric constant of GaAs layer compared to SiO₂. Thanks to these excellent features of MODFET slopein current saturation exceeds the slope MOSFET, which ensures its high performance. Use of MODFET can increase the speed of the VLSI structures in 2,5-3 times.
Design and technology analysis of high performance heterojunction field effect transistors for submicron LSI/VLSI structures
Keywords: польовий транзистор; гетероперехід; арсенід галію; двомірний електронний газ; gallium arsenide; two-dimensional electron gas